2008
DOI: 10.1097/mlg.0b013e318157f764
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Video‐Endoscopy and Surgical Field Grading Scale for Endoscopic Sinus Surgery: A Multi‐Centre Study

Abstract: Standardized video-endoscopy has been demonstrated to significantly improve reliability and reproducibility of results and is recommended for future work evaluating bleeding in ESS. The new Wormald grading scale has been shown to be an inexpensive, reliable, and sensitive tool to rapidly evaluate intraoperative bleeding in ESS. It overcomes several limitations of the Boezaart scale, enabling us to analyze currently employed and newly developed hemostatic methods and agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 19 publications
1
70
0
1
Order By: Relevance
“…The latter measurement modalities even more accurately reflected the efficacy of hemostatic interventions, in that the direct objective of anesthesia in FESS is to render an optimal surgical field rather than to reduce blood loss. Recently, a multi-center standardized reliability analysis verified the interobserver and intraobserver reliability of the Boezaart scale [16].…”
Section: Discussionmentioning
confidence: 99%
“…The latter measurement modalities even more accurately reflected the efficacy of hemostatic interventions, in that the direct objective of anesthesia in FESS is to render an optimal surgical field rather than to reduce blood loss. Recently, a multi-center standardized reliability analysis verified the interobserver and intraobserver reliability of the Boezaart scale [16].…”
Section: Discussionmentioning
confidence: 99%
“…Als Videoendoskopie [115] ist sie auch der digitalen Aufzeichnung zug ä nglich, und erm ö glicht die Auswertung durch unabh ä ngige Untersucher [116] .…”
Section: Endoskopie Und Videoendoskopieunclassified
“…The 11-point Wormald surgical field grading scale was chosen for this study because it has been shown to have a higher reliability than other grading scales [9] . Full intraoperative video was available and completely reviewed in each case.…”
Section: Methodsmentioning
confidence: 99%